Reporting ‘African gangs’: theorising journalistic practice during a multi-mediated moral panic - Koumouris, Gregory (Crime, media, culture, 2022)
This article uses Bourdieusian field theory to examine how journalistic practices contributed to a multi-mediated moral panic about ‘African gangs’ in Melbourne, Australia. Empirical insight is supplied via interviews with journalists who identified traditional media outlets as ‘secondary definers’ that amplified and legitimised this racialised threat construction. Participants attributed the intense and sensationalised media coverage to the political climate, the newsworthiness of racialised ‘folk devils’, and the economic and technological transformation of the journalistic field. These transformations were perceived to have negatively influenced journalistic standards by incentivising the efficient production of commodifiable content. Participants described how these structural changes were filtered through the social personalities of different news outlets; they shaped, and were reproduced through, distinct managerial cultures, editorial routines and journalistic habitus. The emergent nomos (‘rules of the game’) was perceived to constrain the autonomy of journalists, particularly those lacking cultural capital, and limit opportunities for contestation of the ‘African gangs’ narrative. Journalists seemingly adapted by engaging in practices which reflected their attempts to negotiate these conditions and establish coherent narrative identities. In some cases, this entailed the neutralisation of what journalists recognised as ethically questionably reporting practices.